Liposomal angiogenic peptides for ischemic limb perfusion: comparative study between different administration methods. (21st November 2016) - Hwang, Hyosook; Kim, Hyeon-Soo; Jeong, Hwan-Seok; Rajasaheb, Bagalkot Tarique; Kim, Minjoo; Oh, Phil-Sun; Lim, Seok Tae; Sohn, Myung-Hee; Jeong, Hwan-Jeong
Abstract: Background: We investigated the therapeutic effectiveness of PEGylated liposomes loaded with angiogenic peptides for treating hindlimb ischemia. Methods: Rats received a femoral artery occlusion. Red blood cells collected from the animals were labeled with technetium-99m. Limb perfusion gamma imaging was performed. PEGylated liposomes loaded with angiogenic peptides were administered intra-arterially. Technetium-99m red blood cell imaging was repeated 1 week later. The animals were sacrificed the next day. The expression of angiogenic proteins was studied. Later, changes in limb perfusion after intra-arterial infusion versus intra-muscular injection were also compared to determine the therapeutic effectiveness of different administration methods. Results: Femoral artery occlusion dramatically reduced ischemic limb perfusion (by an average of 69%, compared to contralateral limb). This was not different among groups ( p  > 0.05). Liposomes loaded with angiogenic peptides significantly improved ischemic limb perfusion, compared to controls (210% of baseline, versus 100% of baseline in control; p  < 0.05 versus controls). The enhanced ischemic limb perfusion was accompanied by an increased expression of CD 31 (an average of 1.6-fold increase of controls; p  < 0.05). The liposomes or peptides treatment alone did not affect ischemic perfusion (liposomes alone: 100% of baseline; peptides alone: 120% of baseline; p  > 0.05 versus controls, respectively) or the angiogenic response (1.1-fold of controls in liposomes alone; 1.0-fold of controls in peptides alone; p  > 0.05 versus controls, respectively). Intra-muscular injection induced similar liposomal treatment effects on ischemic limb perfusion (230% of baseline) as those by intra-arterial infusion (210% of baseline; p  < 0.05 versus intra-muscular). Conclusions: PEGylated liposomes loaded with angiogenic peptides improved ischemic limb perfusion and promoted angiogenic responses. Liposomal angiogenic treatment via intra-arterial infusion resulted in an equally effective therapeutic efficacy compared to that of intra-muscular injection. These results show the therapeutic potential of our liposomal strategy for treating peripheral limb ischemia.